How does Tra2β protein regulate tissue-specific RNA splicing?. (20th July 2012) - Elliott, David J.; Best, Andrew; Dalgliesh, Caroline; Ehrmann, Ingrid; Grellscheid, Sushma
Abstract : The splicing regulator protein Tra2β is conserved between humans and insects and is essential for mouse development. Recent identification of physiological RNA targets has started to uncover molecular targets and mechanisms of action of Tra2β. At a transcriptome-wide level, Tra2β protein binds a matrix of AGAA-rich sequences mapping frequently to exons. Particular tissue-specific alternatively spliced exons contain high concentrations of high scoring Tra2β-binding sites and bind Tra2β strongly in vitro . These top exons were also activated for splicing inclusion in cellulo by co-expression of Tra2β protein and were significantly down-regulated after genetic depletion of Tra2β. Tra2β itself seems to be fairly evenly expressed across several different mouse tissues. In the present paper, we review the properties of Tra2β and its regulated target exons, and mechanisms through which this fairly evenly expressed alternative splicing regulator might drive tissue-specific splicing patterns.